An Indexical Approach to Architecture - Anne Bordeleau (Footprint)
The paper uses Peirce’s notion of the index and Arendt’s conception of action and reification to cast light on a phenomenological consideration of architecture. The relation that Arendt establishes within a larger historical context between the contemporary reification of art and the socio-political role of action sets up a framework in which the need for a phenomenological approach to architecture is reasserted. In the past two hundred years, from the first age of historicism, marked by nineteenth-century historical relativism, to our second age of historicism, characterised by the recognition of relative historicity, there always were architects who sought the essence of architecture at a fundamentally human and experiential level. It is significant that in a period that wavered between eclectic relativism and rigid objectivism, a situation still felt today, the experience of architecture was consistently considered as an essential means to architecture. How does phenomenology operate beyond the categories of the objective and the relative, between the visible and the tangible?  The paper explores ways in which architecture can physically question the user – is it a trace from the past, an imprint of its time, an index requiring movement for comprehension? Making space for the interpenetration of personal and shared times, the translation of the index in architecture does not dictate meaning or reduce it to an endless play between signifier and signified: it throws the question back to the level of the embodied encounter. Steering clear of a consideration of autonomous constructions, architecture is dynamically considered within a triadic relation that equally involves the architecture itself, the world in which it takes shape, and the people that experience it.